1997
DOI: 10.1007/pl00005679
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence that the reduction in mesencepalic dopaminergic neurons in the weaver heterozygote is not due to a failure in target cell interaction

Abstract: The murine weaver (wv) mutation is characterized by a genetically determined loss of several neuronal populations, which include the nigrostriatal dopaminergic neurons. Animals homozygous for the wv gene exhibit marked deficits in dopaminergic morphological and neurochemical parameters. The wv gene shows incomplete dominance in that heterozygous (wv/+) mice exhibit moderate reductions in midbrain dopaminergic neuron number. It is unclear whether the dopaminergic neuronal loss in homozygous and heterozygous ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
4
0
4
Order By: Relevance
“…Developmental abnormalities have been observed in cerebellum of weaver heterozygote animals ( wv/+ (Rakic & Sidman, 1973 a ; Smeyne & Goldowitz, 1989) even in embryos (Bayer et al 1996). Increased cell death has been observed in cerebellar neurons of the wv/+ animals (Willinger & Margolis, 1985; Wullner et al 1995) as well as in dopaminergic neurons of the mesencephalon (Verina et al 1997; Won et al 1997) but much less than that found in wv/wv animals. In part, the diminished cell death observed in wv/+ animals relative to wv/wv may be due to a gene dosage effect; the heterozygous cells presumably express less GIRK2 wv (Hess, 1996).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Developmental abnormalities have been observed in cerebellum of weaver heterozygote animals ( wv/+ (Rakic & Sidman, 1973 a ; Smeyne & Goldowitz, 1989) even in embryos (Bayer et al 1996). Increased cell death has been observed in cerebellar neurons of the wv/+ animals (Willinger & Margolis, 1985; Wullner et al 1995) as well as in dopaminergic neurons of the mesencephalon (Verina et al 1997; Won et al 1997) but much less than that found in wv/wv animals. In part, the diminished cell death observed in wv/+ animals relative to wv/wv may be due to a gene dosage effect; the heterozygous cells presumably express less GIRK2 wv (Hess, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…High levels of GIRK expression are found in the olfactory bulb, hippocampus, cortex, thalamus and cerebellum (Karschin et al 1996). Identification of the mutation in the GIRK2 wv channel as the causative agent leading to cell death in specific neuronal populations within the substantia nigra and cerebellum has underscored the important role these channels play in normal CNS functions across a broad range of systems (Kofuji et al 1996; Liao et al 1996; Navarro et al 1996; Slesinger et al 1996; Tong et al 1996; Won et al 1997). Although the exact mechanism by which the defect in GIRK2 wv leads to death is still unknown, several possible explanations have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the vermis is the region most severely affected, whereas cell deficit is spared in cerebellar hemispheres (Herrup and Trenkner, 1987; Eisenman et al, 1998; Maricich et al, 1997; Martí et al, 2001). In the heterozygous weavers ( wv /+), neurodegeneration is less evident (Rezai and Yoon, 1972; Rakic and Sidman, 1973a,b; Herrup and Trenkner, 1987; Blatt and Eisenman, 1985; Won et al, 1997; Martí et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the heterozygous weavers (wv/+), neurodegeneration is less evident (Rezai and Yoon, 1972;http://dx.doi.org/10.1016/j.ijdevneu.2015.12.006 0736-5748/© 2016 Elsevier Ltd. All rights reserved. Sidman, 1973a,b;Herrup and Trenkner, 1987;Blatt and Eisenman, 1985;Won et al, 1997;Martí et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Η μετάλλαξη weaver προέκυψε με αυθόρμητο τρόπο το 1961 σε μια αποικία μυών του στελέχους C57BL/6J (Lane, 1964). Πρόκειται για μια υπολειπόμενη αυτοσωμική σημειακή μετάλλαξη με λάθος νόημα, που εντοπίζεται στο 16 ο χρωμόσωμα (Won et al, 1997).…”
Section: To γενετικο μοντελο Weaverunclassified